GERAKAN LITERASI SEKOLAH BERBASIS WEST JAVA LEADER’S READING CHALLANGE - Slam, Zaenul (PD PGMI se Indonesia, 2017)
The purpose of this study was to describe the literary movement based West Java School Leader’s Reading Challenge (WJLRC) in Junior High School 3 Majalengka. This research is a qualitative research. The technique of collecting data through observation, interviews, and documentation. Subjects were the principal, teachers, students, and parents. The data analysis in research through the three stages of data reduction, data presentation, and conclusion. Test the validity of the data is using triangulation sources. The results of this study show that: The first, the motion read into the daily activities of the entire school community. This is evident from: 1) school regularly conducting reading 15 minutes before the lesson begins; 2) available and utilization of facilities and infrastructure reads like a library, a reading corner and others; 3) increasing the number of visits of students and teachers to the library of school ; 4) Implementation of Readhaton / other mass reading activities periodically. The second, the formation of a community of students read through WJLRC This is evident from: 1) increasing the number of books read and made review by students; 2) increasing the speed reading student participants WJLRC activities; 3) the continuity and sustainability of WJLRC between classes. The third, the publication of writings by students and teachers of literacy. It appears from the evidence of the activities and work the students and teachers of literacy on the website WJLRC. The fourth, the growing support of parents and the community to the school literacy movement. This is evident from: 1) the direct involvement of parents and the community in a variety of school activities literacy movements; 2) increasing the support and concern of parents and the community to the efforts of growing culture in homes and communities; 3) the donation of books to the school from parents and the community.